2015
DOI: 10.1016/j.aej.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Improving the rate of Cu+2 recovery from industrial wastewater using a vertical array of reciprocating perforated zinc discs

Abstract: This work investigates the possibility of improving the rate of Cu +2 recovery and/or removal from industrial wastewater by cementation technique using an array of pulsating horizontal perforated zinc discs. The results show that the rate of cementation was found to increase by increasing frequency and amplitude of oscillation (vibrating velocity); disc diameter; copper ion concentration and solution temperature while decreasing by increasing the disc separation. Under certain conditions using pulsating array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In recent years, there has been growing research interest in intensifying the cementation process using various items and configurations such as, ceramic suspended solids [13], bubble column reactor fitted with horizontal screens [14], reactor with perforated baffles [15] or perforated discs [16] as turbulence promoters, reactor equipped with a rotating perforated basket and using alcoholic additives [17], reactor fitted with a plastic jet [18], electromagnetic field [19] or high-speed mixer-disperser capable of providing cavitation effect [20]. However, to the best of our knowledge, a limited number of publications deals with ultrasound-assisted cementation and only one applied on the copper cementation onto iron [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been growing research interest in intensifying the cementation process using various items and configurations such as, ceramic suspended solids [13], bubble column reactor fitted with horizontal screens [14], reactor with perforated baffles [15] or perforated discs [16] as turbulence promoters, reactor equipped with a rotating perforated basket and using alcoholic additives [17], reactor fitted with a plastic jet [18], electromagnetic field [19] or high-speed mixer-disperser capable of providing cavitation effect [20]. However, to the best of our knowledge, a limited number of publications deals with ultrasound-assisted cementation and only one applied on the copper cementation onto iron [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Mubarak et al [9] found that disc reciprocation has increased the rate of cementation of copper on reciprocating horizontal perforated zinc disc by a factor ranging from 2.8 to 5.5 compared to cementation on stagnant disc. Elshazly [10,11] in his investigations for the rate of copper recovery from industrial wastewater by cementation using pulsating zinc cylinders and pulsating vertical parallel plates, found that pulsation has increased the rate of cementation by a factor ranging from 2.5 to 5 and from 2.75 to 4.8, compared to stagnant cylinders and stagnant plates respectively. The present work investigates the effect of using solution pulses on improving the rate of copper ions cementation using a fixed bed of zinc Raschig rings.…”
Section: Introductionmentioning
confidence: 99%